Os cadernos de língua portuguesa da secretaria da educação do estado de São Paulo sob a ótica dos professores do ensino médio - Paccico, Vânia Tadeu (2014)
The object of this research is the Curriculum of Portuguese Language of High School. The aim has been analyzing the meanings that the teachers at this grade level attribute the material. First, we started from the hypotheses that High School teachers have questions about working with the books of Portuguese Language for a few reasons: The teachers do not participated in the processes of capacitance of Curriculum Proposal, the guidelines in the spaces in - service training are not sufficient, the information about the contents and methodology of the proposed curriculum were not properly disclosed to teachers and resistance to take on the books of Portuguese Language proposed by São Paulo Secretary of Education. This is a qualitative research methodology, as a first step refers to the bibliographic and documentary research, analyzing the concepts of curriculum and their conceptions (Moreira & Tadeu, 2001; Gadotti, 2006; Sacristán, 2006; Saviani, 2003; Silva,2004), Curriculum of São Paulo State (2010, 2011), Curriculum of the Portuguese Language of High School with Notebooks Teacher and Student, from official documents such as the National Curricular Parameters of High School (NCPHS), National Curriculum Guidelines of High School (NCGHS) and the Law of Guidelines and Bases of National Education (LGBNE). In addition, In the second stage we used audio taped interview with semi-structured with four teachers who teach Portuguese Language in high school and the teacher coordinator of this level of education in a public school in the Region SUL 2 located in the city of São Paulo. The procedure for data analysis was based on content analysis of Bardin (1994) and Minayo (2009). Finally, the senses that teachers attribute to the Notebooks, after technical orientation, are serving as support for the competencies and skills in the Curriculum proposals of the São Paulo State requiring reformulations in their content for use in the classroom, not being a material to be used to form plasted, so it was concluded that the importance of in-service training on handling the Notebooks Teacher and Student and the need for teachers and managers develop the Political Pedagogical Project is the first step for each School Unit form their identity.